When Would Immunologists Consider a Nanomaterial to be Safe? Recommendations for Planning Studies on Nanosafety. Issue 21 (2nd April 2020) - Himly, Martin; Geppert, Mark; Hofer, Sabine; Hofstätter, Norbert; Horejs‐Höck, Jutta; Duschl, Albert
Abstract: The immune system is professional in recognizing and responding to non‐self, including nanomaterials. Immune responses by professional and nonprofessional immune cells are thus nearly inevitable upon exposure of cells and organisms to such materials. The state of research into taking the immune system into account in nanosafety studies is reviewed and three aspects in which further improvements are desirable are identified: 1) Due to technical limitations, more stringent testing for endotoxin contamination should be made. 2) Since under overdose conditions immunity shows unphysiological responses, all doses used should be justified by being equivalent to tissue‐delivered doses. 3) When markers of acute inflammation or cell stress are observed, functional assays are necessary to distinguish between homeostatic fluctuation and genuine defensive or tolerogenic responses. Since immune activation can also indicate that the immune system considers a stimulus to be harmless and induces tolerance, activation markers by themselves do not necessarily imply a danger to the body. Guidelines such as these are necessary to approach the point where specific nanomaterials are classified as safe based on reliable testing strategies. Abstract : When markers of acute inflammation or cell stress are observed in the presence of nanomaterials, immunological assays are necessary to distinguish between homeostatic fluctuation and genuine defensive or tolerogenic responses. Meaningful data require exclusion of endotoxin contamination, a dose corresponding to that reaching cells in the body, and, if necessary, functional tests.